MUNCULNYA TAREKAT BARU ABAD PERTENGAHAN HINGGA KINI - Bisri Mustofa (Insititut Agama Islam Agus Salim Metro Lampung, 2021)
This essay studies the influence of neosufism on the continuity of tasawuf doctrine and new tarekats emerged during the last two centuries of medieval Islamic period. The raise of the fourteeth century neosufism movement had greatly influenced the nature and the characteristics of the new tasawuf and tarekats of the succeeding era. In addition to giving impetus in ‘purification’ of the doctrines to avoid the tasawuf and tarekat from intrusion of unIslamic elements, the neosufisme has provided with guidance so that they should be kept under the syariat control. This new tendency has forced the tasawuf and tarekats to weaken their support to the doctrin of immanation of God toward His creatures, and replaces it with the transcendent doctrine. The return to the original stipulations of the Qur’an and the Sunna liberated the tasawuf and tarekats from their un islamic characters. The Neosufism movement had succeeded in changing the orientation of the new tasawuf and tarekas to be more responsive to the worldly interest.